FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN DI PT INDONESIA AIR ASIA MEDAN - Safrida . (Jurnal Prodi Fakultas Ekonomi-UISU, 2019)
The formulation of the problem of this research is as follows: How does health and safety affect (K3) to the employee's performance at PT Indonesia Air Asia Medan?, how is the influence of leadership on the performance of PT Indonesia Air Asia Medan employees? How does competency affect employee Kinarja? How does the working environment affect employee performance? How does occupational health and safety affect (K3) and leadership, competence, and working environment in the performance of PT Indonesia Air Asia Medan employees? The objectives of this study are as follows: to know and analyze the impact of occupational health and Safety (K3), leadership, competence and working environment on the performance of employees of PT Indonesia Air Asia Medan. The samples in this study amounted to 60 employees. Data analysis using multiple regression analysis. Based on research conducted on employees of PT. Air Asia Indonesia Medan, the results of research that occupational health and safety, leadership, competence and work environment are positively and significantly affected by employee performance. Keyword : Kinerja Karyawan, Kesehatan dan Keselamatan Kerja (K3),Kepemimpinan, Kompetensi , Lingkungan Kera